The role of information technology in improving human resources performance- An applied research at Al-Rasheed Bank - JASIM, Dr. ALI lSSA (Research Parks Publishers, 2023)
This research aims to determine the role of information technology in improving the performance of human resources, Rasheed Bank was chosen to conduct a field study to diagnose the reality of the use of information technology and the extent of its impact on improving the performance of human resources. The study was applied to a sample of employees working at Rasheed Bank, consisting of 60 people who were chosen randomly. The questionnaire was used as a main tool to collect the necessary data and information. The study can prove the validity of the hypothesis that indicates the existence of a relationship and impact between the two variables. The study showed that the role of information technology in improving the performance of human resources was strong, and there is a logical justification for accepting the main research hypotheses. To achieve this goal, the dimensions of the independent variable information technology were adopted, represented by (physical components, databases, communications networks, software, and human resources), and the dimensions of improving the performance of human resources were adopted, represented by (efficiency, effectiveness, and performance). The research included the following domains: The first domain: Research methodology. The second domain: A conceptual framework for information technology. The third domain: A conceptual framework for improving human resources performance. The fourth domain: The practical aspect. The fifth domain: Conclusions and proposals.